2022
DOI: 10.1101/2022.11.02.514888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ras-dependent RAF-MAPK hyperactivation by pathogenic RIT1 is a therapeutic target in Noonan syndrome-associated cardiac hypertrophy

Abstract: RIT1 belongs to the family of Ras guanosine triphosphatases (GTPases) that regulate many aspects of signal transduction and are drivers of cancer and congenital disorders. RIT1 gain-of-function mutations are found in lung cancer, leukemia, and in the germline of Noonan syndrome individuals with an increased prevalence of cardiac hypertrophy and other congenital heart defects. Pathogenic RIT1 proteins evade proteasomal degradation and promote MEK/ERK mitogen-activated protein kinase (MAPK) hyperactivation, yet … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Our group previously performed CRISPR screens to explore RIT1 genetic dependencies 15 and identified the deubiquitinase USP9X as a genetic regulator of RIT1 function 15 . This finding was particularly interesting given that there is a growing understanding that the protein abundance of RIT1 is important for its function 14,20,21 . Mutant forms of RIT1 evade regulation by the CRL3 LZTR1 complex, thereby increasing RIT1 protein abundance 14 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Our group previously performed CRISPR screens to explore RIT1 genetic dependencies 15 and identified the deubiquitinase USP9X as a genetic regulator of RIT1 function 15 . This finding was particularly interesting given that there is a growing understanding that the protein abundance of RIT1 is important for its function 14,20,21 . Mutant forms of RIT1 evade regulation by the CRL3 LZTR1 complex, thereby increasing RIT1 protein abundance 14 .…”
Section: Discussionmentioning
confidence: 90%
“…USP9X deubiquitinates wild-type and mutant RIT1 ( Figure 4F-G ), thereby increasing RIT1 abundance and stability. Given that protein abundance of RIT1 is important for its function 14,20,21 , USP9X is a key factor in mediating RIT1 -driven oncogenic phenotypes. Our work supports previously known mechanisms of RIT1 regulation by LZTR1 14,20,43 , and we suggest that USP9X and LZTR1 oppose the action of one another in controlling the ubiquitination status of wild-type RIT1 ( Figure 5E ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Cuevas-Navarro and Wagner et al found that wild type and pathogenic mutants of RIT1 associate with the plasma membrane through charge complementarity and this membrane localization is required for RAF interaction and MAPK signaling (27). In HEK293 cells and mouse embryonic fibroblasts, ectopic RIT1 M90I -mediated activation of the MAPK cascade was dependent upon classical RAS proteins (27). The reliance on wild type RAS-and potentially its isoprenylation at the membrane-may underly the identified sensitivity to statins in RIT1-mutant tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that treatment of NS mice with various MEK inhibitors ameliorates craniofacial abnormalities (Ptpn11 Q79R/+ mice treated with U0126 and KRas V14I/+ mice treated with PD0325901) [15,16], hypertrophic cardiomyopathy (KRas V14I/+ , Raf1 L613V/+ , and Sos1 E846K/+ treated with PD0325901/mirdametinib and Rit1 M90I/+ treated with trametinib) [16][17][18][19], growth retardation (KRas V14I/+ and Ptpn11 D61G/+ treated with U0126) [5,16,20], cognitive deficits (Ptpn11 D61G/+ treated with SL327) [21], and lymphatic abnormalities (endothelial-specific Raf1 S259A/+ embryos treated with U0126) [22]. It is important to note that MEK inhibitors appear to be ineffective in certain NS genotypes, such as LZTR1 (vascular-specific Lztr1 −/− treated with pimasertib) [23].…”
Section: Sirolimus (Rapamycin) Mtor Inhibitor Prevention Of Organ Tra...mentioning
confidence: 99%